Inhibitory effect of Atorvastatin on the secretion of extracellular virulence products by Methicillin resistant Staphylococcus aureus - Fraidoon Abdulqader Salih (Zanco Journal of Pure and Applied Sciences, 2021)
Statins are lipid-lowering therapeutic agents that have displayed useful anti-inflammatory and antibacterial properties. The focus of this research study was to understand the role of statins in controlling bacterial pathogenicity. Haemolysins and some other substances secreted by S. aureus were inhibited by Atorvastatin. It was found that Atorvastatin had a negligible effect on the growth of the bacteria at subminimal inhibitory concentrations, meanwhile it significantly reduced the secretion of haemolysins, coagulase and catalase. Thus, Atorvastatin could be used in conjunction with some antibiotics in controlling Methicillin resistant S. aureus MRSA infections and immunomodulation of the defense system.